ACADEMIC CONCERNS, REQUESTED AND RECEIVED SUPPORT AMONG ADOLESCENTS IN THE FOUR WEEKS FOLLOWING CONCUSSION: A PILOT STUDY. Issue 4 (28th April 2020) - Snedden, Traci; Post, Eric; Schmidt, Christian; Brooks, Alison
Background: Even short-term cognitive challenges place adolescents at risk for successful achievement of academic success and attainment of career goals. Studies that have examined subjects receiving follow-up at a concussion or other specialty clinic have noted cognitive issues that cause learning problems upon return to the classroom. However, a gap exists specific to the types of academic concerns and needs for academic support using a prospective longitudinal design in a general sample. Purpose: The purpose of this pilot study was to describe the scope of academic concerns, requested and received academic support over time among adolescents in the four weeks following a concussion injury.Methods : Prospective longitudinal pilot study. Adolescents, aged 13-18 years, and their parent/legal guardian were enrolled within 7 days of concussion injury using a community-based design. Academic effects, requested and received support were assessed by electronic completion of the Concussion Learning Assessment and School Survey (CLASS) of both adolescent and their parent/legal guardian at 4 time points across 28 days, each one week apart. Results: Overall, 37 adolescents (51.4% female, mean age: 16.4±1.4 years) and their parent/legal guardian, provided sufficient data for analysis. A decrease in the frequency of academic concerns over time was noted across the 4 weeks following injury with 37.8% (n=14) reporting challenges in one or more of their classes in the first week after their concussion, compared to 10.8% (n=4) at 28 days. A decrease in requested supports was also noted, with 48.6% (n=18) requesting some form of academic support in the first week compared to 13.5% (n=5) at 28 days. Most commonly requested supports across all time points included extra time to complete work, reduced homework, reduced or waived makeup work, and a shortened school day. Received academic support was also greatest in the first week following concussion (40.5%, n=15) and declined to 16.2% (n=6) at 28 days. Grades were reported as worse since their concussion across all time points with 18.9% reporting this concern at 14 and 21 days. Conclusion: High rates of academic concerns and requested supports were reported in the first week following concussion. In addition, a consistent proportion of students reported a worsening of grades and continued to report academic concerns and needs for academic support four weeks after they sustained a concussion. These pilot findings support the need for greater attention to the academic effects of concussion and related support needs in the classroom for all students. : Table 1. Student and parent responses regarding class/subject-based academic concerns and potential impact on grades during concussion recovery Table 2. Student and parent responses regarding academic supports that were needed during concussion recovery